IMMUNOGLOBULIN SYNTHESIS IN MICE : SUPPRESSION BY ANTI-ALLOTYPE ANTIBODY - Herzenberg, Leonore A. (The Rockefeller University Press, 1967)
In the mouse, antibody directed against an immunoglobulin allotype, Ig-1b, passed from mother to offspring or injected into neonates, suppresses synthesis of immunoglobulin carrying Ig-1b. In allotype homozygotes as well as heterozygotes the allotype suppression is manifested both by a delay of several weeks in attaining initial detectable allotype levels and a reduction in allotype level continuing into adulthood. A possible mechanism for the differentiation of the immune system consistent with both the kinetics of suppression reported here for the mouse and the comparatively longer lived and more complete allotype suppression described for the rabbit is discussed. Evidence for a strong intralitter (as opposed to interlitter) correlation of age of onset of immunoglobulin allotype synthesis is presented.